Study on the spatial differences of methane hydrate dissociation process by depressurization using an L-shape simulator. (1st August 2021) - Cui, Jin-Long; Cheng, Li-Wei; Kan, Jing-Yu; Pang, Wei-Xin; Gu, Jun-Nan; Li, Kun; Wang, Ling-Ban; Sun, Chang-Yu; Wang, Xiao-Hui; Chen, Guang-Jin; Li, Xing-Xun
Abstract: The spatial difference of hydrate dissociation by depressurization was investigated in an L-shape hydrate simulator to enhance the exploitation efficiency of natural gas hydrates. Hydrates were found to dissociate slower near the mining well than far from the mining well due to the higher water saturation. The mass transfer rate of methane molecules in the water phase was much slower than that in the gas phase. In both vertical and horizontal directions, pore water migrated from the location far from the mining well to that near the mining well in the hydrate reservoir under the pressure difference. This led to a lower dissociation rate for the hydrate distributed at the location near the mining well, which was different from the results in gas/petroleum reservoirs and numerical simulations. The spatial difference was more pronounced in the vertical direction than in the horizontal direction. Gravity caused more water migration in the vertical direction, which led to more uneven dissociation of the hydrates. Sediments with higher permeability and lower mining pressure could result in more pronounced spatial differences. These findings can provide deep insights into the spatial evolution of multiple fields during the exploitation of natural gas hydrates. Highlights: A novel L-shape hydrate simulator was designed to study the spatial distribution hydrate. The dissociation of hydrate is faster and is completed earlier at the location far from the mining well. The spatial difference in the vertical direction is more pronounced than in the horizontal direction. The spatial difference was more pronounced in the sediments with larger permeability. Lower mining pressure results in more pronounced spatial difference.